Improvement of personnel management motivational system based on corporate culture - Akhmedov Muzaffar Shokirjonovich (THE INNOVATION ECONOMY, 2026)
This article is devoted to a comprehensive study of the motivational system for managing core production personnel in garment manufacturing enterprises of Namangan region and to the development of well-grounded proposals. The main objective of the research is to examine the motivational systems applied in enterprises of the sector, with particular emphasis on attitudes toward corporate culture, and to propose specific and practical solutions